Various Dimensions of Folk Life in Surdas' Poetry : सूर-काव्य में लोक-जीवन के विविध आयाम - Meena , Tulsi Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In Hindi literature, Mahatma Surdas has been greatly revered, yet critical analysis explaining the significance of the great poet Surdas remains scarce. Like every great poem, Sur's poetry demands understanding rather than mere reverence. The interpretation of Surdas' poetry, as left by scholars like Ramchandra Shukla and Hazari Prasad Dwivedi, has not progressed much beyond their initial assessments. Acharya Shukla’s critique marked the beginning of identifying the distinctive nature of Sur's poetry. He analyzed Sur’s sensitivity, imagination, deep emotional engagement, creative innovation in new themes, linguistic expertise, and extraordinary poetic expression, thereby paving the way for critical evaluation of Sur’s literary work. However, his criticism also carried certain biases that influenced later analyses of Sur's poetry. One such assertion was that Sur's poetry lacked social engagement. Acharya Shukla wrote, "Surdas was deeply engrossed in his emotions and did not engage in a critique of the surrounding circumstances. He did not pay much attention to what was happening in the world, the tendencies of the people, or the direction in which society was heading." Abstract in Hindi Language: हिंदी साहित्य में महात्मा सूरदास को तो बहुत सम्मान मिला है, लेकिन महाकवि सूरदास के महत्व की व्याख्या करने वाला आलोचनात्मक विवेक विरल ही है। हर अच्छी कविता की तरह सूर की कविता भी श्रद्धा से अधिक समझ की मांग करती है। रामचंद्र शुक्ल और हजारीप्रसाद द्विवेदी ने सूर के काव्य की व्याख्या को जहाँ छोड़ा था वहाँ से आज भी वह बहुत आगे नहीं बढ़ी है। आचार्य शुक्ल की आलोचना से सूर की कविता के विशिष्ट स्वरूप की पहचान की शुरुआत हुई। उन्होंने सूर की सहृदयता, कल्पनाशीलता, तन्मयता, नवीन प्रसंगों की उद्भावना शक्ति, वाग्विदग्धता और काव्यभाषा की अपूर्व सृजनशीलता की व्याख्या करते हुए सूर-साहित्य की आलोचना का मार्ग बनाया। लेकिन उनकी आलोचना में कुछ ऐसे आग्रह भी हैं, जिनसे सूर की परवर्ती आलोचना भी प्रभावित हुई है। उनका एक आग्रह यह है कि सूर के काव्य में लोक-संग्रह का अभाव है। आचार्य शुक्ल ने लिखा है-”सूरदास जी अपने भाव में मग्न रहने वाले थे, अपने चारों ओर की परिस्थिति की आलोचना करने वाले नहीं। संसार में क्या हो रहा है, लोक की प्रवृत्ति क्या है, समाज किस ओर जा रहा है, इन बातों की ओर उन्होंने अधिक ध्यान नहीं दिया है।” Keywords: महात्मा सूरदास, काव्य, लोक-जीवन, सहृदयता, कल्पनाशीलता, तन्मयता।